Purificação e caracterização de uma nova fosfolipase A2 ácida da peçonha de Bothrops pauloensis - Rodrigues, Renata Santos (2006)
Phospholipases A2 (PLA2) is small enzymes that present molecular mass around 15kDa and are found in a variety of biological and cellular fluids as fluid sinovial, macrophages, platelet, pancreatic tissue, among others. The present work describes the purification and chemical, biological and enzymatic characterization of an acidic phospholipase A2 of Bothrops pauloensis snake venom. New fosfolipase A2 was called BP-PLA2, this enzyme was purified by ionic exchange in CM-Sepharose Fast Flow followed for hidrophobic chromatography in Phenyl Sepharose CL-4B and finishing in C8 reverse-phase column. BP-PLA2 consists of a protein of 15.8kDa and isoelectric point of 4.34. The N-terminal sequences of the enzyme displayed a significant homology with the Asp-49 acid of other snake venoms in first fifteen amino acids. The catalytic activity of the BP-PLA2 was 315 U/mg, showing a considerable increase of activity PLA2 and was capable to induce high indirect hemolytic activity in the different intervals of time. Acidic phospholipase A2 was capable to inhibit platelet aggregation at the presence of collagen, fact not occurred when this enzyme was incubated with ADP, showed a sufficiently sharp edematogenic activity in paw mice. BP-PLA2 induced miotoxic effect, being the characterization carried through for creatine kinase (CK) levels and morphological analyses. These studies had indicated an increase of the creatine kinase levels in 1 hour and the histological analyses had indicated that the PLA2 induced an intense edema with evident leucocitary infiltration and damage in the muscular cells after 24 hours of injection of the toxin.